2016
DOI: 10.1007/s13365-016-0449-0
|View full text |Cite
|
Sign up to set email alerts
|

Natalizumab-treated patients at high risk for PML persistently excrete JC polyomavirus

Abstract: Sixty-three natalizumab-treated patients with relapsing multiple sclerosis were screened for JC polyomavirus (JCV) viruria. Urinary-positive patients were longitudinally sampled for up to 24 weeks. Using methods that distinguish encapsidated virus from naked viral DNA, 17.5 % of patients were found to excrete virus, consistent with the prevalence of urinary excretion in the general population. Unexpectedly, urinary excretion was predominantly seen (>73 %) in patients with high JC antibody index (≥2.0). Active … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…In 2016, Campagnolo et al reported that PML incidence increased by 0.067 per month until September 2013 but only 0.027 from September 2013 to June 2016, a 50% decrease in the slope of the curve. No methodologic details were given on how incidence was calculated, but we found from a previous paper that each point was computed from the total number of PML cases and the total exposure to natalizumab . Recently updated results confirm a stabilization of this incidence rate since mid-2016 …”
Section: Discussionmentioning
confidence: 99%
“…In 2016, Campagnolo et al reported that PML incidence increased by 0.067 per month until September 2013 but only 0.027 from September 2013 to June 2016, a 50% decrease in the slope of the curve. No methodologic details were given on how incidence was calculated, but we found from a previous paper that each point was computed from the total number of PML cases and the total exposure to natalizumab . Recently updated results confirm a stabilization of this incidence rate since mid-2016 …”
Section: Discussionmentioning
confidence: 99%
“…Despite attempts to utilize this tool to stratify risk and aid in decision-making to start or stop drug, the incidence of PML associated with natalizumab does not appear to be decreasing substantially [53]. This said, one must consider competing variables before assuming lack of efficacy, including more use of natalizumab over time-both number of exposures and duration that individual patients may be treated with drug.…”
Section: Jcv Antibody Testingmentioning
confidence: 99%